Development Of The Common Hardware And Software Architecture For The Distributed Version Of The Ontology-Based Portal (Journal of Information Technologies in Education (ITE), 2009)
Development of the distributed version of the Ontology-Based Portal for Management of Education and Scientific Resources of MESU is considered. The substantiations of the hardware and software architecture are given. Analysis of the modern IT technologies and software for designing, creation and testing of the ontology-based information systems, efficiency evaluation of architecture distributed at data and ontology level is presented.
Keywords: architecture; clustering; distributed information system; ontology-basedl portal; semantic technologies